Oncogenic potential of macrophage-capping protein in clear cell renal cell carcinoma - Chen, Zhuang-Fei (Mol Med Rep, 2021)
Macrophage-capping protein (CapG) is a newly characterized oncogene involved in several types of cancer. However, the expression patterns and biological mechanisms of CapG in clear cell renal cell carcinoma (ccRCC) are unclear. The present study aimed to investigate the roles of CapG in the prognosis, proliferation and metastasis of ccRCC. In the present study, the expression of CapG was analyzed by western blotting in 24 paired ccRCC and adjacent normal tissue samples. Another 152 tissue samples from 152 patients with ccRCC were examined by immunohistochemistry. Compared with normal tissue, CapG expression was significantly increased in ccRCC tissue, and high CapG expression was associated with advanced tumor stage, histological grade, lymph node metastasis, and poor overall survival. Moreover, CapG was an independent predictor of survival. Lentivirus-mediated CapG knockdown significantly inhibited 786-O cell proliferation, migration, and invasion, induced cell cycle arrest at the G(2)/M phase, and increased apoptosis in vitro. Microarray analysis indicated that RAC, CDC42 and ERK/MAPK signaling were disrupted by CapG knockdown in 786-O cells. In conclusion, the present findings indicate that CapG plays an oncogenic role in ccRCC and may represent a potential therapeutic target for this disease.